European Xylella fastidiosa Strains Can Cause Symptoms in Blueberry - Shantharaj, Deepak (Plant disease, 2024)
Strains of the bacterial pathogen Xylella fastidiosa subspecies multiplex (Xfm) and pauca (Xfp) isolated from symptomatic almond and olive plants in Spain and Italy were used in this study. Because of the risk of host jump and considering the importance of southern highbush blueberry production in Spain, we tested a small set of these strains for their potential to infect and cause disease symptoms in blueberries under greenhouse experiments. Xfm IVIA5901 (isolated from almonds in Alicante, Spain) caused symptoms similar to those caused by Xfm AlmaEm3 (isolated from blueberries in Georgia, U.S.A., and used as a reference strain capable of inducing severe symptoms in blueberry). Nevertheless, bacterial populations of Xfm IVIA5901 in planta were significantly lower than those of Xfm AlmaEm3. Xfm ESVL (isolated from almonds, Alicante, Spain) and Xfp XYL1961/18 (isolated from olives, Ibiza Island, Spain) caused limited symptoms, while Xfm XYL466/19 (isolated from wild olives, Mallorca Island, Spain) and Xfm XF3348 (isolated from almonds, Mallorca Island, Spain) and Xfp De Donno (isolated from olives, Puglia, Italy, and representative of the devastating olive quick decline syndrome) did not cause symptoms nor colonize blueberries. This study suggests that certain strains already found in Europe could infect blueberry if conditions conducive for a host jump in this region are met, such as proximity of blueberries to other infected hosts and presence of insect vectors that feed on these crops. Surveys on the presence of X. fastidiosa in blueberries in Spain and other European countries are needed to anticipate possible issues